2015
DOI: 10.3389/fnmol.2015.00014
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral vectors as tools to understand central nervous system biology in mammalian model organisms

Abstract: Lentiviruses have been extensively used as gene delivery vectors since the mid-1990s. Usually derived from the human immunodeficiency virus genome, they mediate efficient gene transfer to non-dividing cells, including neurons and glia in the adult mammalian brain. In addition, integration of the recombinant lentiviral construct into the host genome provides permanent expression, including the progeny of dividing neural precursors. In this review, we describe targeted vectors with modified envelope glycoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 127 publications
1
54
0
Order By: Relevance
“…The viral vector that is infused in a given brain location to enable optogenetic stimulation typically involves either a lentivirus (LV) or adeno‐associated virus (AAV), which have different properties with associated advantages and disadvantages for future clinical applications. LV has a relatively large particle size (100 nm), which restricts its diffusion through neural tissue (Parr‐Brownlie et al, ). This property of LVs is useful when the aim is to transduce neurons in a small nucleus.…”
Section: Optogenetic Development and Current Applicationsmentioning
confidence: 99%
“…The viral vector that is infused in a given brain location to enable optogenetic stimulation typically involves either a lentivirus (LV) or adeno‐associated virus (AAV), which have different properties with associated advantages and disadvantages for future clinical applications. LV has a relatively large particle size (100 nm), which restricts its diffusion through neural tissue (Parr‐Brownlie et al, ). This property of LVs is useful when the aim is to transduce neurons in a small nucleus.…”
Section: Optogenetic Development and Current Applicationsmentioning
confidence: 99%
“…Lentiviruses have larger packaging capabilities, permitting the use of transcriptional promoters to target expression neuronal types, an approach not available with AAVs [125]. Cell-type specific promoters however may not a drive sufficient amount of expression [126].…”
Section: Expression Methodsmentioning
confidence: 99%
“…However, it depends on the size and growth rate of the cell. This confluence is to ensure that the cells have enough space to divide during transduction, which takes about 96 h. A previous study showed that cell confluence of more than 50% limits the interaction of lentivirus, cells, and DNA complex [39]. On the other hand, cell confluence of less than 30% will slow down cell growth [40].…”
Section: Basic Conditions Of Gene Silencingmentioning
confidence: 99%